Interaction between caveolin-1 polymorphism and dietary fat quality indexes on visceral adiposity index (VAI) and body adiposity index (BAI) among overweight and obese women: a cross-sectional study - Rasool Ghaffarian-Ensaf; Farideh Shiraseb; Atieh Mirzababaei; Cain C. T. Clark; Khadijeh Mirzaei (BMC, 2022)
Abstract Background and aims Caveolin-1 (CAV-1) in adipocyte tissue and other body parts possesses numerous biological functions. In the present study, we sought to investigate the interaction between CAV-1 polymorphism and dietary fat quality indexes on visceral adiposity index (VAI) and body adiposity index (BAI) among overweight and obese women. Methods This study was conducted on 386 women aged 18-48 years old. Biochemical measurements were assessed by standard protocols. We used a food frequency questionnaire (FFQ) to calculate the dietary intake and the indexes of dietary fat quality intake. Anthropometric values and body composition were measured by standard methods. Finally, the CAV-1 genotype was measured using the PCR-RFLP method. Results We found marginally significant differences between AA and GG genotypes of waist-to-hip ratio (WHR) (P = 0.06) and BAI (P = 0.06) of participants after adjusting for potential confounders. For dietary intakes, after adjusting with the energy intake, mean differences in biotin (P = 0.04) and total fiber (P = 0.06) were significant and marginally significant, respectively. The interaction between two risk alleles (AA) with omega-6 to omega-3 ratio (W6/W3) on BAI, after adjustment for potential confounders (age, physical activity, energy intake, education), was marginally positive (β = 14.08, 95% CI = − 18.65, 46.81, P = 0.07). In comparison to the reference group (GG), there was a positive interaction between the two risk alleles (AA) with W6/W3 ratio on VAI (β = 2.81, 95% CI = 1.20, 8.84, P = 0.06) in the adjusted model. Conclusions We found that there might be an interaction between CAV-1 genotypes with dietary quality fat indexes on VAI and BAI among overweight and obese women.